2018
DOI: 10.1111/jocn.14145
|View full text |Cite
|
Sign up to set email alerts
|

Clinical leadership and nursing explored: A literature search

Abstract: Clinical Leadership and an understanding on how clinical leaders contribute to the health service is central to the application of values-based practice and how clinical leaders impact on innovation, change and making care better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
165
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(174 citation statements)
references
References 43 publications
7
165
2
Order By: Relevance
“…For Staff and Care Delivery, our findings indicate staff grades do not put as much importance on this as their senior managers, nor do they perceive this being performed highly in practice. This is somewhat at odds with previous findings (Larsson & Sahlsten, ; Stanley & Stanley, ) and may be due to the “invisible” nature of this type of work known as “informal leadership” (Larsson & Sahlsten, ). Patient safety is an important aspect of clinical leadership.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…For Staff and Care Delivery, our findings indicate staff grades do not put as much importance on this as their senior managers, nor do they perceive this being performed highly in practice. This is somewhat at odds with previous findings (Larsson & Sahlsten, ; Stanley & Stanley, ) and may be due to the “invisible” nature of this type of work known as “informal leadership” (Larsson & Sahlsten, ). Patient safety is an important aspect of clinical leadership.…”
Section: Discussioncontrasting
confidence: 79%
“…This is described as an informal leadership role (Larsson & Sahlsten, 2016). Previously, researchers found that staff nurse grades expressed a need to advance skills in clinical leadership and were in key positions to positively influence patient care (Casey, McNamara, Fealy, & Geraghty, 2011;Chavez & Yoder, 2015;Stanley & Stanley, 2018). Staff grades view recognized leaders (managers) as "gatekeepers" for the enablement of initiatives (Harvey et al, 2019); however, clinical patient issues that are important to staff may not be embraced by managers and hence not performed.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Many of the negative qualities were identified in prior studies, with Carney (), Fealy et al, (), Stanley () and Stanley (, ), all suggesting that effective CL was hampered by a lack of confidence (Stanley & Stanley, ), communication problems, blurred role boundaries, a lack of clinical experience and clinicians that were not respected. A number of participants expressed a degree of role conflict around their leadership and management roles (Firth, ; Stanley, ) with one participant saying, “they felt like the meat in the sandwich” (P12), torn between their managerial and CL responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…While a significant number of previously published research papers were located that outlined; the attributes of clinical leaders (Carney, ; Cook, ; Patrick, Laschinger, Wong, & Finegan, ; Stanley, , ; Won, ); definitions of clinical leadership (Cook & Leathard, ; Fealy et al, ; Stanley, ; Stoddart, Bugge, Shepherd, & Farquharson, ); models to support an understanding of clinical leadership (Cook, ; Leigh et al, ; Patrick et al, ); the focus of clinical leader activity in practice (Jeon et al, ; Patrick et al, ; Stanley, Cuthbertson, & Latimer, ; Stanley, Latimer, & Atkinson, ; Stoddart et al,; Supamanee, Krairiksh, Singhakhumfu, & Turale, ); and barriers to effective clinical leadership (Bender, ; McNamara et al, ; Stanley, , ), no papers outlining research specifically describing clinical leadership in a rural and remote context were identified. A number of publications that detailed a review of previously published research papers on the topic of clinical leadership were also identified (Chavez & Yoder, ; Davidson, Elliott, & Daly, ; Mannix, Wilkes, & Daly, ; Solange & Voce, ; Stanley & Stanley, ; Stavrianopoulos, ); however, here too, nothing was found to illuminate the connection between CL and rural and remote health or the practice of clinical leadership in rural and remote practice environments. It was because of this and the authors experience in a R&R environment that the study was developed.…”
Section: Introductionmentioning
confidence: 99%
“…RNs' leadership in municipal home health care implies that they lead, prioritize, allocate, coordinate, teach and participate in nursing care with older adults, next of kin and the care team [6,7]. Nursing leadership, clinical leadership and health care leadership are terms evident in nursing [8]. There is a need to focus on developing strong leadership in the nursing profession across the globe [9].…”
Section: Introductionmentioning
confidence: 99%